Rethinking Education for a More Inclusive and Future-Ready AI Era - Oyetade, Kayode; Zuva, Tranos (African Journal of Inter/Multidisciplinary Studies, 2025)
This study examines the evolving role of education in preparing learners for an AI-driven future within the context of the fourth industrial revolution (4IR) and the potential of genera-tive artificial intelligence (gAI). As AI increasingly reshapes labor markets, education systems must move beyond traditional, indus-trial-age models to cultivate adaptive, ethical, and future-ready competencies. Guided by connectivism, social constructivism, and transformative learning, the study employs a descriptive literature review to identify essential competencies, including AI literacy, digital fluency, critical thinking, ethical reasoning, and lifelong adaptability. It evaluates how current educational practices, policies, and curricula address these demands. The analysis draws on global examples and contextual insights from the Global South, with a particular focus on South Africa, highlighting curriculum reforms, upskilling and reskilling strategies, and inclusive policy interventions. Findings reveal both the opportunities and systemic challenges of AI integration, including digital inequities, underprepared educa-tors, and misaligned curricula. The study concludes by proposing a strategic, phased framework for educational transformation that integrates ethical governance, teacher capacity-building, interdisci-plinary learning, and cross-sector collaboration, thereby positioning education as a driver of inclusive, responsible, and socially respon-sive engagement in the era of gAI.